Evidence-based best-practice guidelines for preventing anterior cruciate ligament injuries in young female athletes: A systematic review and meta-analysis - Petushek, E. J.; Sugimoto, D.; Stoolmiller, M.; Smith, G.; Myer, G. D. (The American Journal of Sports Medicine, 2019)
Background: Injury prevention neuromuscular training (NMT) programs reduce the risk for anterior cruciate ligament (ACL) injury. However, variation in program characteristics limits the potential to delineate the most effective practices to optimize injury risk reduction. Purpose: To evaluate the common and effective components included in ACL NMT programs and develop an efficient, user-friendly tool to assess the quality of ACL NMT programs. Study Design: Systematic review and meta-analysis. Methods: Study inclusion required (1) a prospective controlled trial study design, (2) an NMT intervention aimed to reduce incidence of ACL injury, (3) a comparison group, (4) ACL injury incidence, and (5) female participants. The following data were extracted: year of publication, study design, sample size and characteristics, and NMT characteristics including exercise type and number per session, volume, duration, training time, and implementer training. Analysis entailed both univariate subgroup and meta-regression techniques using random-effects models. Results: Eighteen studies were included in the meta-analyses, with a total of 27,231 participants, 347 sustaining an ACL injury. NMT reduced the risk for ACL injury from 1 in 54 to 1 in 111 (odds ratio [OR], 0.51; 95% CI, 0.37-0.69]). The overall mean training volume was 18.17 hours for the entire NMT (24.1 minutes per session, 2.51 times per week). Interventions targeting middle school or high school-aged athletes reduced injury risk (OR, 0.38; 95% CI, 0.24-0.60) to a greater degree than did interventions for college- or professional-aged athletes (OR, 0.65; 95% CI, 0.48-0.89). All interventions included some form of implementer training. Increased landing stabilization and lower body strength exercises during each session improved prophylactic benefits. A meta-regression model and simple checklist based on the aforementioned effective components (slope = -0.15, P = .0008; intercept = 0.04, P = .51) were developed to allow practitioners to evaluate the potential efficacy of their ACL NMT and optimize injury prevention effects. Conclusion: Considering the aggregated evidence, we recommend that ACL NMT programs target younger athletes and use trained implementers who incorporate lower body strength exercises (ie, Nordic hamstrings, lunges, and heel-calf raises) with a specific focus on landing stabilization (jump/hop and hold) throughout their sport seasons. Clinical Relevance: Clinicians, coaches, athletes, parents, and practitioners can use the developed checklist to gain insight into the quality of their current ACL NMT practices and can use the tool to optimize programming for future ACL NMT to reduce ACL injury risk.